2021
DOI: 10.1371/journal.ppat.1009585
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection, neuropathogenesis and transmission among deer mice: Implications for spillback to New World rodents

Abstract: Coronavirus disease-19 (COVID-19) emerged in late 2019 in China and rapidly became pandemic. As with other coronaviruses, a preponderance of evidence suggests the virus originated in horseshoe bats (Rhinolophus spp.) and may have infected an intermediate host prior to spillover into humans. A significant concern is that SARS-CoV-2 could become established in secondary reservoir hosts outside of Asia. To assess this potential, we challenged deer mice (Peromyscus maniculatus) with SARS-CoV-2 and found robust vir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 52 publications
(64 reference statements)
7
82
0
5
Order By: Relevance
“…These are among the most well-studied mammals in North America, in part due to their status as zoonotic reservoirs for multiple zoonotic pathogens and parasites [116][117][118]. Experimental infection, viral shedding, and sustained intraspecific transmission of SARS-CoV-2 were recently confirmed for P. maniculatus [51,52], but similar studies have not been conducted for P. leucopus, which is widely distributed across the eastern United States and Mexico.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are among the most well-studied mammals in North America, in part due to their status as zoonotic reservoirs for multiple zoonotic pathogens and parasites [116][117][118]. Experimental infection, viral shedding, and sustained intraspecific transmission of SARS-CoV-2 were recently confirmed for P. maniculatus [51,52], but similar studies have not been conducted for P. leucopus, which is widely distributed across the eastern United States and Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…Our model predictions matched the results of several recently published in vivo studies on SARS-CoV-2 infection (Figure 1). For instance, experiments on deer mice (Peromyscus maniculatus; [51,52]) and raccoon dogs (Nyctereutes procyonoides; [47]) confirmed SARS-CoV-2 infection and transmission to naive conspecifics. Our model also estimated a high probability of zoonotic capacity of American mink for SARS-CoV-2 (Neovison vison, probability=0.83, 90th percentile), in which farmed individuals present severe infection from human spillback, and demonstrate the capacity to transmit to conspecifics as well as to humans [11,46].…”
Section: Comparing Model Predictions To In Vivo Outcomesmentioning
confidence: 99%
“…Further details are provided under Supplementary Methods for Molecular Modelling. We then compared our insilico findings with experimental results reported by different research groups with mouse adapted strains/isolates [6][7][8]13,[21][22][23][24][25][26][27][28][29] and VOC 14,[30][31][32][33][34] (Table 1). Taken together, we were able to gain valuable insights into the likely effects of different mutations of consequence.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies in mice showed that the neurotropic influenza virus could invade the CNS from the respiratory mucosa and the vagus nerve directly [ 130 ]. SARS-CoV-2 was directly injected into deer mice, and immunohistochemistry examinations showed the presence of SARS-CoV-2 in trigeminal ganglionic neurons, neurons, and microglia of the afferent nerves, and the glomerular layer of the olfactory bulb, indicating that this virus may enter into the brain via the gustatory-olfactory-trigeminal pathway [ 131 ]. SARS-CoV-2 was also shown to invade the CNS in rhesus monkeys primarily via the olfactory bulb, subsequently spreading to multiple brain regions, including the hippocampus, thalamus, and medulla oblongata, and causing neuroinflammation and local pathological changes [ 132 ].…”
Section: The Potential Mechanisms Underlying the Invasion Of Sars-cov-2 Into The Nervous Systemmentioning
confidence: 99%